209k views
1 vote
What is the solution to : 3 ( 10 x − 14 ) = 9 ( 2 x + 2 ) ?

A.-7
B.2
C.-0.5
D.5

User Lmocsi
by
6.2k points

1 Answer

4 votes
Let's solve it step by step:

3( 10x − 14 ) = 9( 2x + 2 )

First, we can try to remove the multipliction outsude brackets to avoid complicating the steps.

(10x - 14x) = 9(2x + 2)/3

(10x - 14x) = 3(2x +2)

Then we can multiply 3 into the bracket on left hand side to remove the brackets.

10x - 14 = 3(2x) + 3(2)

10x -14 = 6x + 6

Put the unknown together:

10x - 6x = 6 + 14

4x = 20

x = 5

Therefore, the answer is D. x = 5.

Hope it helps!
User Dick Fox
by
6.6k points